Proteomic Analysis of Lactobacillus nagelii in the Presence of Saccharomyces cerevisiae Isolated From Water Kefir and Comparison With Lactobacillus hordei - Bechtner, Julia; Xu, Di; Behr, Jürgen; Ludwig, Christina; Vogel, Rudi F. (Frontiers in Microbiology, 2019)
Water kefir is a slightly alcoholic and traditionally fermented beverage, which is prepared from sucrose, water, kefir grains, and dried or fresh fruits (e.g. figs). Lactobacillus (L.) nagelii, L. hordei and Saccharomyces (S.) cerevisiae are predominant and stable lactic acid bacteria and yeasts, respectively, isolated from water kefir consortia. The growth of L. nagelii and L. hordei are improved in the presence of S. cerevisiae. In this work we demonstrate that quantitative comparative proteomics enables the investigation of interactions between LAB and yeast to predict real-time metabolic exchange in water kefir. It revealed 73 differentially expressed (DE) in L. nagelii TMW 1.1827 in the presence of S. cerevisiae. The presence of the yeast induced changes in the changes in the carbohydrate metabolism of L. nagelii and affected reactions involved in NAD+/NADH homeostasis. Furthermore, the DE enzymes involved in amino acid biosynthesis or catabolism predict that S. cerevisiae releases glutamine, histidine, methionine and arginine, which are subsequently used by L. nagelii to ensure its survival in the water kefir consortium. In co-culture with S. cerevisiae, L. nagelii profits from riboflavin, most likely secreted by the yeast. The reaction of L. nagelii to the presence of S. cerevisiae differs from that one of the previously studied L. hordei, which displays 233 differentially expressed proteins, changes in citrate metabolism and an antidromic strategy for NAD+/NADH homeostasis. So far, aggregation promotion factors, i.e. formation of a specific glucan and bifunctional enzymes were only detected in L. hordei.